Communication Skill-Based Writing Instruction (Csbwi) To Promote Extrovert Students in Writing - Vike Aprilianin Marwintaria Saputri; Ayu Andriyaningsih; Widiyanto; Wistina Seneru; Rapiadi (Syntax Corporation, 2023)
This study aims to discover the relationship between extrovert students' and their writing ability at the university level. The study was conducted from March to April 2023 at the Jinarakkhita Buddhist College Bandar Lampung. The population of the research was the second-semester Buddhist Education Department students in the academic year 2022-2023. The researchers used a rubric score to analyze and measure the students' recount text writing ability before and after treatment. The data were collected by administering essay writing pre-tests and post-tests. The data were collected from a writing test used to assess students' writing abilities, and a series of analyses were performed, beginning with examining the reliability of the questionnaire and the association between the score and students' personalities. The result showed increased pre-test and post-test average scores from 49.9 to 65.1. In addition, this study found that second-semester students' writing abilities have improved due to the use of communication skill-based writing instruction (CSBWI) to promote extrovert students' as they are more expressive in conducting ideas.